Higher education leadership and uncertainty during the COVID-19 pandemic - Iwan Nugroho; Niken Paramita; Belay Tizazu Mengistie; Oleksandr P Krupskyi (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
The impact of the pandemic on higher education activities is a major concern around the world. Higher education is obliged to carry out the necessary measures of adaptation, innovation, and management change, which are promoted by leaders at various levels. The leadership is further committed to encouraging transformative changes to meet students’ most critical needs.  Leadership is expected to be able to use all resources in the organization, even in limited conditions due to pandemic impacts.  The crisis condition during pandemic become the main approach in implementing higher education leadership.  First, the leader develops effective multi-directional communication to mediate and respond to actual needs and changes, especially involving parties impacted or affected by policy changes.  Second, the leader develops a cooperation network to support mutually one another to form productivity. It is necessary to network with all interests to formulate the best solution to reduce the adverse impacts of the pandemic.  Third, the leader develops empathy to encourage the work environment, increase productivity, and combine efforts to promote health on their personal and professional sides. Fourth, lecturers develop an own set of heuristics for managing their classes using technology as the main work in the new normal situation.JEL Classification A23; I00; I23